ADDING LEMON VERBENA (ALOYSIA CITRIODORA) LEAVES POWDER TO THE DIET AND ITS EFFECT ON THE PRODUCTIVE PERFORMANCE OF BROILER - Zahraa Amer Al-Bahadli, Zahraa Amer Al-Bahadli; Huda Qasim Al-Hamdani , Huda Qasim Al-Hamdani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This experiment was conducted to compare the addition of different levels of Aloesia citriodora leaf powder and the antibiotic oxytetracycline to the feed on the productive performance of broilers. The experiment was conducted in the poultry field of the Department of Animal Production at the College of Agricultural Engineering. Sciences - University of Baghdad (Abu Ghraib) during the period from 10/29/2022 until 12/10/2022 for a period of 42 days,. In the study, 300 one-day-old unsexed broiler chicks (ROSS 308) were used. The chicks were randomly distributed among five treatments and five replications. One replicate contained 12 chicks, and the treatments were as follows: T1: control, T2: diet with the addition of oxytetracycline powder at a rate of 250 mg/kg feed, the treatment of T3, T4, and T5 diets with the addition of Aloysia Citriodora leaves powder at a rate of 1, 1.5 and 2%, respectively. The results showed that there was a significant increase (P